CORRECTIONAL WORK WITH CHILDREN WHO HAVE SPEECH DISORDERS (DYSARTHRIA) - Ganieva Gulrukh Tavakkaljon qizi (Bright Mind Publishing, 2025)
This article examines the methods, strategies, and pedagogical approaches used in the correctional work with children who have speech disorders, specifically dysarthria. It discusses the nature and causes of dysarthria, its impact on communication and learning, and the role of speech therapists and educators in overcoming speech difficulties. Special attention is given to individualized correctional programs, integration of speech therapy with educational activities, and collaboration between specialists, teachers, and parents. The article also highlights effective exercises and techniques for improving articulation, breathing, and phonation in children with dysarthria, aiming to enhance their overall communicative competence and social adaptation.
Keywords: Dysarthria, speech disorders, correctional work, speech therapy, special pedagogy, articulation development, communication skills, inclusive education, pedagogical support.